PEDIATRIC HEMATOLOGY: TYPES OF LEUKEMIA AND MODERN TREATMENT APPROACHES - Kurbankulov Uktam Muhammadovich (Web of Journals Publishing, 2025)
This article examines the major types of leukemia observed in pediatric patients and highlights modern treatment approaches currently utilized in clinical practice. It provides an overview of acute and chronic forms of childhood leukemia, including Acute Lymphoblastic Leukemia (ALL), Acute Myeloid Leukemia (AML), Chronic Myeloid Leukemia (CML), and rare subtypes. Special attention is given to recent advancements in diagnostics, targeted therapy, immunotherapy, and bone marrow transplantation. The article aims to present updated, evidence-based information to assist healthcare professionals in understanding current trends in pediatric leukemia management.
Keywords: Pediatric hematology; childhood leukemia; Acute Lymphoblastic Leukemia (ALL); Acute Myeloid Leukemia (AML); Chronic Myeloid Leukemia (CML); immunotherapy; targeted therapy; bone marrow transplantation; modern treatment.